From cultural industries to creative economy: The popular culture within the public policy - Tomka Goran (University Educons, Faculty of Sports and Tourism, Novi Sad, 2014)
Lately, creative industries have become an extremely popular concept in cultural policies across the globe. For many, it came as a surprise. However, the idea of merging culture and arts with industrial production has been slowly evolving during the 20th century, thus there is not much space for a surprise. The aim of this paper is to position creative industries in a broader historical and theoretical framework. The paper is looking at the interplay of popular culture and public (cultural) policies: from the post-war critical theory of the Frankfurt school and UNESCO's early debate on cultural industries to the recent policies and theories on creative economy and creative industries.